IMPLEMENTASI GAYA KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH DI MTS ISLAMIC CENTER CIREBON - Ida Parida Ida; Siti Ayu Ikasari; Duriyah (IAIC (Institut Agama Islam Cirebon), 2022)
This study aims to determine the implementation of the principal's situational leadership style at MTs Islamic Center Cirebon. The type of research used in this research is descriptive research with a qualitative approach. Data collection techniques in this study used non-participant open observation, semi-structured interviews and documentation studies. The results of this study indicate that the principal has implemented a situational leadership style, from indicators that the principal's role as telling (telling) has been implemented, selling (peddling), participating (involving) and delegating (delegating). The implementation of the situational leadership style in accordance with the level of readiness or maturity of educators and education staff will make the principal's leadership more effective in achieving the goals of educational institutions.